Hubungan dan Pengaruh Ibu Karir Terhadap Stimulasi Sosial Emosional Pada Anak Usia Dini Melalui Permainan Peran Edukatif - Salsabila, Najwa; Sianturi, Risbon; Ramjani, Ai Asti; Ayulia, Dea (Sekolah Tinggi Agama Islam Al-Kifayah Riau, 2025)
This study aims to examine the relationship and influence of working mothers on the socio-emotional stimulation of early childhood through educational role-play. Employing a mixed-methods approach with both quantitative and qualitative types, the subjects were 100 working mothers with children aged 3–6 years, and the object of the study was children's socio-emotional development. Data were collected through observation, interviews, and questionnaires, then analyzed using descriptive qualitative methods and quantitative correlation tests. The results indicated a significant positive correlation between the involvement of working mothers in Type A educational role-play and the socio-emotional development of their young children. Another finding revealed that the quality of mother–child interaction had a greater impact than the quantity of time spent together. In conclusion, educational role-play serves as an effective medium for working mothers to stimulate socio-emotional aspects in early childhood